Bentuk Perlindungan Hukum Terhadap Korban Tindak Pidana Perundungan Melalui Media Sosial - Regita, Dhea Ayu; Widowaty, Yeni (Universitas Muhammadiyah Yogyakarta, 2024)
The development of social media can make it easier for bullies to interact on social media which can harm others, so a legal umbrella is needed to protect victims of bullying in the media. Legal Protection provides rights and assistance to create a sense of security for victims. However, there are still no clear provisions regarding legal protection for victims of bullying through social media. So this study needs to be conducted in order to find out what factors cause bullying through social media and how legal protection is provided for victims of bullying through social media. This study was conducted using a normative research method using legal materials in the form of primary, secondary, and tertiary legal materials which were analyzed in a systematic form. The results of the study showed that 2 important factors were found causing bullying on social media, namely external and internal factors. Furthermore, legal protection for victims of bullying on social media has been regulated in Article 27 of the ITE Law and Article 7A of the Witness and Victim Protection Law where victims have the right to receive physical and psychological protection and receive restitution or compensation. The legal protection carried out by the Ministry of Law and Human Rights is preventive in nature in the form of legal counseling and guidance to ensure the provision of legal aid in accordance with legal aid service standards.